IL-15 reprogramming compensates for NK cell mitochondrial dysfunction in HIV-1 infection - Moreno-Cubero, E; Alrubayyi, A; Balint, S; Ogbe, A; Rowland-Jones, SL; Borrow, P; Dustin, M (American Society for Clinical Investigation, 2024)
Dynamic regulation of cellular metabolism is important for maintaining homeostasis and can directly influence immune cell function and differentiation, including NK cell responses. Persistent HIV-1 infection leads to a state of chronic immune activation, NK cell subset redistribution, and progressive NK cell dysregulation. In this study, we examined the metabolic processes that characterize NK cell subsets in HIV-1 infection, including adaptive NK cell subpopulations expressing the activating receptor NKG2C, which expand during chronic infection. These adaptive NK cells exhibit an enhanced metabolic profile in HIV-1– individuals infected with human cytomegalovirus (HCMV). However, the bioenergetic advantage of adaptive CD57+NKG2C+ NK cells is diminished during chronic HIV-1 infection, where NK cells uniformly display reduced oxidative phosphorylation (OXPHOS). Defective OXPHOS was accompanied by increased mitochondrial depolarization, structural alterations, and increased DRP-1 levels promoting fission, suggesting that mitochondrial defects are restricting the metabolic plasticity of NK cell subsets in HIV-1 infection. The metabolic requirement for the NK cell response to receptor stimulation was alleviated upon IL-15 pretreatment, which enhanced mammalian target of rapamycin complex 1 (mTORC1) activity. IL-15 priming enhanced NK cell functionality to anti-CD16 stimulation in HIV-1 infection, representing an effective strategy for pharmacologically boosting NK cell responses.